Development and Preliminary Validation of a Stroke Physical Activity Questionnaire - Thunyakamon Phusuttatam; Jittima Saengsuwan; Pajeemas Kittipanya-ngam (Stroke Research and Treatment, 2019)
Objective. The aim of the current study was to develop and then to determine preliminary validity of a physical activity questionnaire specifically designed for ambulatory, chronic stroke patients. Methods. This cross-sectional study recruited 92 chronic stroke patients. In Phase I, the SPAQ was developed and its content validity index (CVI) determined. In Phase II, we examined (1) the concurrent validity of SPAQ vs. the International Physical Activity Questionnaire-Short Form (IPAQ-SF); (2) the convergent validity of SPAQ vs. the Functional Ambulation Category (FAC), vs. the six-minute walk test (6-MWT), vs. the timed up and go test (TUGT), vs. the Motricity Index, vs. the National Institutes of Health Stroke Scale (NIHSS), and vs. the Modified Rankin Scale (MRS); and (3) the discriminant validity of the SPAQ vs. the Montreal Cognitive Assessment (MoCA). The concurrent validity and convergent and divergent validity were analysed using Spearman’s rank correlation coefficient. The agreement between the SPAQ and IPAQ-SF was assessed using the Kappa statistic. Results. The SPAQ has 12 items in 3 main components which covers low (7 items), moderate (3 items), and vigorous (2 items) physical activity. The SPAQ had a CVI of 0.93. Spearman’s correlation coefficient (rs) for SPAQ vs. IPAQ-SF was 0.53 (p < 0.001). The SPAQ yielded substantial agreement with the IPAQ-SF (Kappa = 0.65). For convergent validity, the SPAQ had a moderate correlation with the 6-MWT, MI, NIHSS, FAC, TUGT, and MRS (p < 0.05). For discriminant validity, the SPAQ was not correlated with the MoCA (rs = 0.061, p = 0.68). Conclusion. The SPAQ can be used to practically assess physical activity in chronic stroke patients, and it has acceptable psychometric properties which are comparable to other standard physical activity questionnaires. Future work should determine the validity of the SPAQ using an objective device such as an accelerometer.